PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI STMIK ADI UNGGUL BHIRAWA (AUB) SURAKARTA - Anton Respati Pamungkas (STIE AUB Surakarta, 2013)
The Purpose of this study was to examine the influence of organizational culture and compensation to job satisfaction and employees performance at STMIK AUB Surakarta. This research was a survey. The data used were primary data by sampling to employees at STMIK AUB Surakarta. Data collection instruments such as questionnaires measured by a Likert scale, the questionnaires were sent to 30 respondents. Data analysis methods were tested with test validity, reliability test, partial test (t test), Test of simultaneously (test F), R-square test and analysis test track. t test results as follows: 1. The Organizational Culture Variable significantly influenced to Job Satisfaction, 2. Compensation significantly influenced to Job Satisfaction, 3. Organizational culture significantly influenced employees performance, 4. Compensation did not significantly influence on employees performance, 5. Job Satisfaction did not significantly effect on performance. F test result indicated that the Organizational Culture, Job Satisfaction, Compensation had simultaneously significant impact on employees performance. R square test showed a yield of 0.891 meant that performance was explained by the Organization culture, Compensation and Job Satisfaction as an intervening variable had 89.1% and the remaining 10.9% was explained by other variables outside of the model. The test result showed a path analysis 1. The direct effect of the performance, organizational culture 0.690 was greater than the indirect effect on Performance, Organizational Culture mediated with Job satisfaction of -0.005. 2. The direct effect of compensation to the performance of 0,117 was greater than the indirect effect of Compensation to Performance Job satisfaction with mediation of -0.008. 3. Total organizational culture influenced on performance through satisfaction of 0.685 4. Total Compensation effect on performance through the satisfaction of 0.168. Keywords: Cultural Organization, Compensation, Job Satisfaction and Employee Performance